Evaluation of Influence of Wall Slip on Measurement of Rheological Parameters by Means of a Hydrodynamic Measuring System - Hanna Krykh; Halyna Matiko; Lyudmyla Sadovska (Energy Engineering and Control Systems)
The technique for processing the output signals of hydrodynamic measuring system of rheological parameters of non-Newtonian fluids is presented in the paper. Hydrodynamic measuring system is built on four serially connected bridge hydrodynamic converters. The paper shows that the error of determination of rheological parameters directly from the experimental flow characteristic in consistent variables is considerable if the non-Newtonian fluid has the effect of wall slip on measuring surfaces of sensors of bridge transducers. The technique for processing the output signals of the measuring system enables to detect the wall slip and to correct the values of fluid flow-rate in each bridge hydrodynamic converter using the values of the wall slip coefficient. Corrected flow characteristic is the basis for the determination of rheological parameters of controlled fluid. The influence of wall slip on the evaluation of rheological model of non-Newtonian fluid and results of measurement of its parameters are analyzed in the paper. It is shown that taking into account the effect of wall slip significantly improves measuring accuracy of rheological parameters.